Roman gems and finger-rings made of gold and glass from Nicea in Bithynia (south-eastern Marmara) - Fatih Hakan Kaya; Ergün Laflı; Martin Henig; Musa Albayrak (Studia Antiquitatis et Medii Aevi Incohantis)
In this brief paper 22 objects comprising Roman engraved gemstones and finger-rings made of both gold and glass are presented, all of which are curated in the Archaeological Museum of İznik in south-eastern Marmara, Turkey. These objects are significant as very few gemstones have been published from Bithynia. Two of the finds were excavated from a necropolis area of Nicaea. A catalogue of these artefacts will be provided at the end of this paper.